EKSISTENSI AGUNAN DALAM PEMBIAYAAN MUDHARABAH PADA LEMBAGA KEUANGAN SYARIAH - Yosi Aryanti (El-Rusyd, 2018)
he concept of mudharabah in sharia financial institutions is not fully inaccordance with the concepts in classical fiqh. such as Sharia Financial Institutions(LKS) applying the concept of mudharabah in financing, the bank acting as shahibulmaal ask for a guarantee or collateral to mudharib, whereas according to some ImamMadzhab forbade it. The National Sharia Council (DSN) is an institution in which itconsists of scholars, practitioners and experts in its field, who are given the task ofinstilling Syar'i values in products run by LKS and monitoring all transactions applied inLKS. Implementation of guarantee on mudharabah financing based on DSN fatwa no. 07 DSN-MUI / IV / 2000. The existence of Collateral is basically not an obligation, in theprocess it becomes a must when customers want to get financing. This is what underliesthe author to see the existence of collateral in mudharabah financing in LKS. Thisresearch is a descriptive analytic research using data about mudharabah financingcontract implementation, books, documents, works, or writings relevant to this studythen analyze it from the perspective of Islamic law